Ultrasonographic measurement of the vascular wall thickness and intima-media thickness in patients with Behçet’s disease with symptoms or signs of vascular involvement: A cross-sectional study - Serdar KAYMAZ; Halil YILMAZ; Furkan UFUK; Ayşe Rüksan ÜTEBEY; Veli ÇOBANKARA; Uğur KARASU; Canan ALBAYRAK YAŞAR; Firdevs ULUTAŞ (Archives of Rheumatology, 2021)
Objectives: This study aims to measure and compare bilateral carotid intima-media thickness (CIMT), bilateral jugular, common femoral, and main portal vein wall thicknesses (VWTs) in Behçet’s disease (BD) patients with and without vascular involvement to obtain a cut-off value for vascular complications and determine their relationship with disease activity. Patients and methods: Sixty-three BD patients (41 males, 22 females; median age: 38.0 years; min 20 - max 71 years) and 30 healthy control subjects (14 males, 16 females; median age: 40.3 years; min 21 - max 60 years) were included in this cross-sectional study between February and March 2020. According to imaging findings, BD patients were divided into two groups as those with and without vascular complications. Disease duration, medical treatment and BD manifestations of patients were questioned. Disease activity was evaluated using the Behçet’s Disease Current Activity Form (BDCAF) and the Behçet’s Syndrome Activity Scale (BSAS). Two radiologists blinded to the diagnosis of BD used ultrasound to measure VWT and CIMT. Receiver operating characteristics were assessed to obtain sensitivity and specificity values for each VWT and CIMT. Results: The groups were similar in terms of age, sex, and body mass index (p>0.05). There was a significant difference between the BD groups when the BDCAF and BSAS scores were compared, while there was no difference between them in terms of disease duration and medical treatment (p>0.05). All VWTs and CIMTs were significantly higher in patients with BD compared to healthy controls (p<0.05). There was no significant difference between the BD groups in terms of CIMT, jugular and common femoral VWTs (p>0.05). But portal VWT was significantly higher in patients with vascular involvement (p<0.05). A cut-off value of ≥1.35 mm yielded a sensitivity of 79.2% and a specificity of 82.4% for the diagnosis of vascular involvement with the highest Youden’s index (area under the curve, 0.869; 95% confidence interval, 0.783 to 0.956). Conclusion: Portal VWT has high sensitivity and specificity for the screening of vascular involvement in patients with BD.